2016
DOI: 10.21071/edmetic.v6i1.5807
|View full text |Cite
|
Sign up to set email alerts
|

La producción científica sobre Realidad Aumentada, un análisis de la situación educativa desde la perspectiva SCOPUS

Abstract: Resumen:Esta investigación pretende revisar las evidencias científicas sobre la implementación de la tecnología de Realidad Aumentada (RA) desde una perspectiva educativa, para ello se ha tomado como instrumento de recogida de información, el repositorio bibliográfico Scopus. El procedimiento es de corte descriptivo sobre una muestra n=1336 referencias de artículos, comunicaciones en conferencias, libros y capítulos de libros. Los resultados de naturaleza cuantitativa muestran las principales áreas temáticas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 1 publication
1
15
0
9
Order By: Relevance
“…With regard to language, the one used by scientists to present their research is English, as found in other studies [33]. The studies are presented via communication and articles, evenly, with the first being slightly more common-results that are consistent with other studies that also add a paper as a type of relevant study [3], with quantitative studies being the main methodological choice [38]. For sources of origin, "INTED proceedings" (3.62%) and "EDULEARN proceedings" (2.36%) are the most common.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…With regard to language, the one used by scientists to present their research is English, as found in other studies [33]. The studies are presented via communication and articles, evenly, with the first being slightly more common-results that are consistent with other studies that also add a paper as a type of relevant study [3], with quantitative studies being the main methodological choice [38]. For sources of origin, "INTED proceedings" (3.62%) and "EDULEARN proceedings" (2.36%) are the most common.…”
Section: Discussionmentioning
confidence: 91%
“…Technology is currently in a moment of great development in the field of education, as a result of the continuous advances that are occurring in techno-pedagogical matters that promote its inclusion in learning spaces [1], where technology is increasingly attaining greater use in training activities [2] thanks to its ubiquitous and ergonomic nature [3]. All this has led to new student activities, not only in the way they communicate and collaborate with their teachers and peers but also in the way they interact with contents in a digital way [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other research through meta-analysis [22][23][24][25][26][27][28][29][30][31] provides evidence and relevant information on the progress of this emerging technology in teaching/learning processes. Wu, Lee, Chang and Liang [32] detail learning activities related to augmented reality with innovative approaches and active participation with pedagogical approaches quite different from the teacher-centered approach [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the teaching methodology, most teachers use traditional techniques and resources, far from a generalized use of technological methodologies (Cubillo et al, 2014;Fombona & Pascual, 2017). This implies a traditional typology, where the teacher reproduces models based on the lecture and the unidirectional transmission of information.…”
Section: Discussionmentioning
confidence: 99%
“…Under this premise, ICT allows the optimization of learning spaces thanks to its potential interactive and socializing characteristics that allow learners to build autonomously their learning (Cabero, 2017). Technology also makes it possible for students to be able to search for information ubiquitously, that is, without limitation of space and time (Fombona & Pascual, 2017).…”
Section: Introductionmentioning
confidence: 99%